PELAKSANAAN PENGUKURAN ARAH KIBLAT OLEH KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI KALIMANTAN BARAT TAHUN 2016-2020 DI KOTA PONTIANAK - Putri, Hesty Kesuma; Hasan, Muhammad; Wibowo, Arif (Institut Agama Islam Negeri (IAIN) Pontianak, 2022)
The purpose of this study is to determine the service procedures, methods and results of the accuracy of the Qibla direction implementation by the Regional Office of the Ministry of Religion of West Kalimantan Province in 2016-2020 in Pontianak City. This study uses a qualitative descriptive research method. Data analysis techniques are carried out in stages starting from data reduction, data presentation, conclusions and verification. Furthermore, all data were checked for validity using data triangulation and member check techniques. The results of this study indicate: 1) The service procedure for measuring the Qibla direction is stated in the SOP for the Qibla Direction Measurement Service. The SOP is included in the type of administrative SOP and the core information has met the 4W+1H criteria; 2) The implementation of the Qibla direction measurement is entirely using the theodolite method; and 3) The results of the accuracy of sixty-one mosques that have been measured and certified by the Regional Office of the Ministry of Religion of West Kalimantan Province are 88.52% very accurate, 9.84% accurate, 1.64% inaccurate. This research is feasible because the previous researchers mainly examined the accuracy of the Qibla direction at one or more mosques in a certain location, while the researchers in this study focused on the process and results of the implementation of the Qibla direction measurement by the Regional Office of the Ministry of Religion of West Kalimantan Province in 2016-2020 in Pontianak City.